Социология профессий и изучение проблем эволюции профессиональных стандартов и норм в постсоветской науке - Инджиголян, А.А.; Ветштейн, С.С. (Изд-во КарГУ, 2012)
Мақалада кəсіптік əлеуметтану əлеуметтанудың дамуындағы жаңа бағытының теориялық негіздерінің қалыптасуы баяндалады. Кəсіпті зерттеудегі кездесетін айырықша ерекшеленетін теориялық бағыттар: американдық, англо-еуропалық, кеңестік дəстүрлер тұрғысынан қарастырылады. Сондай-ақ қазіргі Қазақстандағы, Ресейдегі «ғалым» кəсібінің реструктуризация мəселесі талданып, кəсібі бар жəне жоқ адамдар, нарық пен билік арасындағы қарым-қатынастарындағы кездесетін мəселелері (қиындықтары) айқындалады. Article is devoted the statement of the basic theoretical bases of a new direction in development of sociology — sociology of profession. In this article it was considered distinctive features of approaches to studying of professions by different theoretical traditions: American, English-European, and Soviet. It was analyzed the problems of re-structuring of a «scientist» profession in modern Kazakhstan and Russia and the problems arising in the environment of interaction between professionals, nonprofessionals, the market and the power. The authors use the case study method to illustrate the evolution of post soviet history of science, showing the complex process of forming a new professional identity scientist. The article concludes on the need to support the building of professional scientific subculture in Kazakhstan.